Causes of Stillbirth and its Frequency in Tertiary Care Hospital - Salma Zaman, Rabia Iram, Nazia Sajjad, Tuba Rasheed (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To evaluate the causes of still birth and its frequency in tertiary care hospital. Study design: Descriptive study. Place and duration of study: Department of Obstetrics & Gynaecology, Services Institute of Medical Sciences, Lahore from 1st January 2020 to 30th September 2022. Methodology: Seven thousand women were enrolled from which 100 were identified to have stillbirth and followed up till their outcome of delivery. Those women who had still birth were further followed for the causes related with still birth through their and the fetal clinical available data. All major causes were addressed related with still birth and noted in the proforma. The frequency of the cases was identified through the measurement of incidence rate. Neonates born were clinically evaluated in terms of their birth weight as well as term analysis. Results: Majority of the pregnant women were within the age group of 36-45 years. There were 54% of the women who were obese. On analysis of the associated reasons with still birth, it was observed that 27% of the pregnant women undergoing still birth were not known of the cause, while 24% and 20% had placental complication and infection respectively. Conclusion: Maternal age, infection, placental abruption and obesity are the main causes of still birth. The frequency of still birth is 1.42% in this region. Keywords: Cause, Stillbirth, Frequency